Optimal timing of allogeneic hematopoietic stem cell transplantation in patients with myelodysplastic syndrome. Issue 7 (30th May 2013) - Alessandrino, Emilio Paolo; Porta, Matteo G. Della; Malcovati, Luca; Jackson, Christopher H; Pascutto, Cristiana; Bacigalupo, Andrea; Teresa van Lint, Maria; Falda, Michele; Bernardi, Massimo; Onida, Francesco; Guidi, Stefano; Iori, Anna Paola; et al.
<x xml:space="preserve">Abstract</x> Allogeneic hematopoietic stem cell transplantation (HSCT) represents the only curative treatment for patients with myelodysplastic syndrome (MDS), but involves non‐negligible morbidity and mortality. Registry studies have shown that advanced disease stage at transplantation is associated with inferior overall survival. To define the optimal timing of allogeneic HSCT, we carried out a decision analysis by studying 660 patients who received best supportive care and 449 subjects who underwent transplantation. Risk assessment was based on both the International Prognostic Scoring System (IPSS) and the World Health Organization classification‐based Prognostic Scoring System (WPSS). We used a continuous‐time multistate Markov model to describe the natural history of disease and evaluate the effect of allogeneic HSCT on survival. This model estimated life expectancy from diagnosis according to treatment policy at different risk stages. Relative to supportive care, estimated life expectancy increased when transplantation was delayed from the initial stages until progression to intermediate‐1 IPSS‐risk or to intermediate WPSS‐risk stage, and then decreased for higher risks. Modeling decision analysis on WPSS versus IPSS allowed better estimation of the optimal timing of transplantation. These observations indicate that allogeneic HSCT offers optimal survival benefits when the procedure is performed before MDS patients progress to advanced disease stages. Am. J. Hematol. 88:581–588, 2013. © 2013 Wiley Periodicals, Inc.